The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.jid.2019.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Function-Blocking RHAMM Peptides Attenuate Fibrosis and Promote Antifibrotic Adipokines in a Bleomycin-Induced Murine Model of Systemic Sclerosis

Abstract: Functionblocking RHAMM peptides attenuate fibrosis and promote anti-fibrotic adipokines in a bleomycininduced murine model of systemic sclerosis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…c. Increased COL1A1 expression: Wu et al (2021) found that in BLM-treated mice, NPI-110 and NPI-106 decreased Col1a1 mRNA expression by 11-fold and 14-fold, respectively (P < 0.001). In addition, the authors found that both RHAMMblocking peptides reduced Col1a1-to-Col3a1 ratio to the control ratio (NPI-106) or below the control ratio .…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 98%
See 3 more Smart Citations
“…c. Increased COL1A1 expression: Wu et al (2021) found that in BLM-treated mice, NPI-110 and NPI-106 decreased Col1a1 mRNA expression by 11-fold and 14-fold, respectively (P < 0.001). In addition, the authors found that both RHAMMblocking peptides reduced Col1a1-to-Col3a1 ratio to the control ratio (NPI-106) or below the control ratio .…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 98%
“…This protein was initially isolated from fibroblasts and has been expressed in a variety of human tissues, including thymus, lymph node, tonsil, small intestine, colon, skin, bone marrow, placenta, and testis (Chen et al, 2018). Wu et. al.…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the interactions of HA with its various receptors control the effect of HA on cells. For example, the HA-binding protein, named receptor for hyaluronan-mediated motility (RHAMM), has been shown to stimulate the migration of tumor cells [32], fibroblasts [33], and macrophages [34] and to contribute to myofibroblast differentiation [35] in remodeling tissue. Furthermore, the interaction of HA with RHAMM and CD44 was shown to enhance stem cell migration and proliferation [36], but also inflammatory and fibrotic processes [34,37].…”
Section: Introductionmentioning
confidence: 99%